Psychological disorders, adverse childhood experiences and parental psychiatric disorders in children affected by headache: A systematic review. (September 2022) - Polese, Daniela; Belli, Arianna; Esposito, Dario; Evangelisti, Melania; Luchetti, Anna; Di Nardo, Giovanni; Parisi, Pasquale; Bruni, Oliviero
Abstract: Background: Pediatric headaches have been linked to adverse life events or psychological factors in children and their families, with a complex and bidirectional association. Moreover, it is well-known that psychological stress can trigger headaches. Methods: We searched three databases for studies focusing on headaches and adverse events or psychological factors in children up to 12 years old or in their caregivers. Results: We included 28 studies. Child psychological factors, including internal and external symptoms, were commonly associated with all types of headaches. Sleep disturbances showed a positive association with headaches in 3 out of 5 studies. Family conflict and unhappiness were frequently found in children suffering with headaches, while single-parent families and divorce were not associated. Stressful environments and adverse life events, particularly bullying, were also found to be linked with headaches. Conclusions: Childhood headaches represent an alarm bell for clinicians to investigate and treat psychological or psychiatric disorders in children and their family. Further studies are needed to elucidate the role of early-life adverse events in children and their families. Highlights: Evidences show connections between childhood headache and adverse childhood experiences. Headache is associated to school-related stress and being bullied. Family conflict and unhappiness are associated with headache. Single-parent family and divorce are not connected with headache. Internalising symptoms were frequently found in children with headache.